2010
DOI: 10.1007/s00114-010-0672-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional correlates and mate acquisition role of multiple sexual traits in male collared flycatchers

Abstract: The information content of a sexual signal may predict its importance in a multiple signal system. Many studies have correlated sexual signal expression with the absolute levels of nutrient reserves. In contrast, the changes of nutrient reserves associated with signal expression are largely unknown in the wild due to technical limitations although they are important determinants of signal information content. We compared two visual and eight acoustic sexual traits in male collared flycatchers to see whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 77 publications
5
43
1
3
Order By: Relevance
“…It is sexually selected, but it seems that its information content differs between populations. Our results show that male forehead patch size did not predict lifetime offspring recruitment, and this result is consistent with those of earlier studies performed in this population, suggesting that the forehead patch is a poor indicator of phenotypic quality in our birds (Hegyi et al 2002(Hegyi et al , 2006a, but see Hegyi et al 2010), in contrast to the Swedish population (Gustafsson et al 1995; also see Gustafsson and Qvarnström 2006). It is possible that the advantage of a large forehead patch can only be detected in extra-pair paternity, for example if large-patched males sire more extra-pair young that return to breed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is sexually selected, but it seems that its information content differs between populations. Our results show that male forehead patch size did not predict lifetime offspring recruitment, and this result is consistent with those of earlier studies performed in this population, suggesting that the forehead patch is a poor indicator of phenotypic quality in our birds (Hegyi et al 2002(Hegyi et al , 2006a, but see Hegyi et al 2010), in contrast to the Swedish population (Gustafsson et al 1995; also see Gustafsson and Qvarnström 2006). It is possible that the advantage of a large forehead patch can only be detected in extra-pair paternity, for example if large-patched males sire more extra-pair young that return to breed.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas studies in a population in Gotland, Sweden, showed that the size of this trait was a good indicator of phenotypic quality (Gustafsson et al 1995;Qvarnström 1999; also see Gustafsson and Qvarnström 2006), this is not the case in our population (Hegyi et al 2002(Hegyi et al , 2006a, although the trait is an important determinant of social mating success (Hegyi et al 2010). The male forehead patch size was estimated as the product of its maximum height and maximum width.…”
Section: Study Species and Field Methodsmentioning
confidence: 54%
“…Furthermore, none of the previous studies on carotenoid-based pigmentation have taken into account the biochemical parameters of the physiological variables that could interact with parasitisation in the regulation of the expression of ornamental carotenoids. Plasma biochemical characterisation provides relevant information on the nutrition and condition of the organism or of different organs and, although widely used in clinical diagnosis, is employed only rarely in studies on behavioural ecology (but see, for example, Alonso-Á lvarez et al 2002;Hegyi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies aiming at exploring the determinants of various song features in this species failed to find strong roles for repertoire size in sexual selection despite the fact that males can produce up to 50 syllable types, of which most are specific to individuals (Garamszegi et al, , 2006(Garamszegi et al, , 2008. Interestingly, males with higher repertoire size seem to be less attractive for females, as they pair later than males with songs composed of fewer syllable types (Hegyi et al, 2010). Contrary, features of song output, such as song rate and song length have shown many biologically meaningful correlations (Garamszegi et al, , 2006.…”
Section: Introductionmentioning
confidence: 83%